2002
DOI: 10.1007/bf02976947
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses and nitric oxide production in cerebral ischemic rats

Abstract: We investigated that the role of nitric oxide (NO) on ischemic rats in brain and heart. Ischemia was induced by both common carotid arteries (CCA) occlusion for 24h following reperfusion. Then tissue samples were removed and measured NOx. In brain, NOx was increased by about 40% vs. normal and it was significantly inhibited by aminoguanidine, selective iNOS inhibitor. This result showed that NOx concentration was increased by iNOS. We investigated the role of Ca2+ during ischemia. Nimodipine, L-type calcium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Another investigation has reported that nimodipine (0.3 mg/Kg, i.p.) did not inhibit the increases of NO concentration during ischemia, suggesting that increased NO was due to induction of Ca 2+ -independent NOS (56). Analysis of the effects of nimodipine (i.v.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Another investigation has reported that nimodipine (0.3 mg/Kg, i.p.) did not inhibit the increases of NO concentration during ischemia, suggesting that increased NO was due to induction of Ca 2+ -independent NOS (56). Analysis of the effects of nimodipine (i.v.…”
mentioning
confidence: 98%
“…Of 14 studies investigating the effect of pharmacological treatment in ischemia-induced brain damage, 10 (44-53) reported a positive effect of nimodipine and four did not (54)(55)(56)(57). Another investigation has assessed only the displacement of 1,4-dihydropiridine Ca 2+ channel binding sites, labeled by (+)-[ 3 H]PN 200-110, after oral administration of nimodipine.…”
mentioning
confidence: 99%
“…These results were consistent with the reported anxiolytic effects of NOS inhibitors [ 18 , 19 ] and compatible with the reports of Bonassoli et al [ 22 ] and Gonzaga et al [ 23 ] revealing that infusion of a nonselective NOS inhibitor, a selective nNOS inhibitor, or a selective inducible NOS (iNOS) inhibitor (N-([3-(aminomethyl)phenyl]methyl) ethanimidamide dihydrochloride) into the dorsolateral periaqueductal gray matter or into the dorsal raphe nucleus, respectively, attenuated EtOHW anxiety in rats 24 or 48 hours after discontinuation of EtOH. The expression of iNOS is induced in response to inflammatory and immune stimuli [ 29 ], and chronic EtOH may cause dysregulation of the immune system in the brain that can persist over a certain withdrawal time, while increased production of proinflammatory factors has shown to sensitize EtOHW anxiety [ 30 32 ]. However, in the present study, we did not examine the involvement of solitary iNOS, since it was not detected in the NTS of the protracted EtOHW rats in a preliminary experiment.…”
Section: Discussionmentioning
confidence: 99%